The generation of dual-wavelength fiber lasers and their applications / Amirah binti Abd. Latif - Amirah, Abd. Latif (2013)
This thesis describes the methods and processes of generating tunable single wavelength and dual-wavelength fiber lasers by using two different types of gain media. They are erbium doped fiber (EDF) and semiconductor optical amplifier (SOA) with each of them working as near to homogeneous and inhomogeneous broadening transition gain media respectively. Various single wavelength and dual-wavelength fiber lasers (DWFLs) designs using different selective elements namely tunable banpass filter (TBF), compression and tensile strain FBGs (CTS-FBGs) and arrayed waveguide grating (AWG) are also discussed and compared in the thesis in terms of their output power, side mode suppression ratio (SMSR) and tunability. To generate single wavelength fiber lasers is not a problem compared to the generation of dual-wavelength fiber laser in a homogeneous gain medium. Therefore, cavity loss control method, as a new and novel approach is proposed to overcome the mode competition issue faced by EDF for generation of balanced dual-wavelength output. The generation of DWFL by using SOA is also presented in the thesis which is free from mode competition issue, which however fairs badly in terms of output power performance. This is presented as an alternative way of generating the DWFL. The DWFLs have a lot of applications in various fields including fiber sensors and communications.In this study, new designs of DWFLs for various applications are presented. They are the generation of single longitudinal mode fiber laser for potential application in iii Terahertz ray, the generation of DWFL for wavelength conversion, the generation of DWFL for a minute shifts temperature sensor and also the generation of DWFL for microwaves generation. This is achievable due to a high stability and high quality of the fiber laser in terms of output powers and high value of SMSR.